Static cyclic behaviour of FRP-confined crumb rubber concrete columns. (15th April 2016) - Youssf, Osama; ElGawady, Mohamed A.; Mills, Julie E.
Highlights: Behaviour of FRP-confined CRC columns subject to seismic loading was investigated. CRC provides an environmentally-friendly alternative to conventional concrete. Similar behaviour for both FRP-confined CRC and conventional was observed. Increasing the FRP-confinement thickness increased the column plastic hinge length. High and uniform dilation demand was observed in the FRP-confined CRC columns. Abstract: An experimental study was performed to investigate the possible use of crumb rubber concrete (CRC) for structural columns by evaluating the use of fibre reinforced polymer (FRP) confinement as a means of overcoming the material deficiencies (compressive strength). Five reinforced concrete columns having 240 mm diameter and 1500 mm shear span were tested under axial compression and incrementally increasing reverse cyclic loading. Three columns were constructed out of CRC with 0, 2 and 4 layers of carbon FRP and two were constructed out of conventional concrete with 0 and 2 layers of carbon FRP. The results of this study showed that at the same confinement thickness, the peak strength of the FRP-confined CRC column was slightly higher than that of the FRP-confined conventional concrete column, even though the base concrete compressive strength was less. However, its ultimate drift was slightly lower. Doubling the confinement thickness increased the peak strength and the ultimate drift of the FRP-confined CRC by 11.5% and 53.8%, respectively. By using 2 layers of FRP, the strength confinement effectiveness of the conventional concrete and the CRC were 1.11 and 1.13, respectively, however, the drift confinement effectiveness was 0.98 and 1.07, respectively. This investigation demonstrates that CRC provides an environmentally-friendly alternative to conventional concrete in structural applications.